Diseño y aplicación de una guía metodológica que desarrolle las nociones lógico-matemática en el primer año de básica paralelo “a” del jardín fiscal mixto “Marianita Albán Armas” del cantón Saquisilí durante el año lectivo 2010-2011” - Ortíz Chicaiza, Jenny del Rocío (2011)
The present investigative work contains two main aspects for developing the logical-mathematical notions in the first grade of basic education children, by means of learning tools, ludic activities since it is one of the most accepted activities in the children. The following investigation was applied on the first basic grade , class “A”, at the “Marianita Albán Armas”, Saquisilí, after having detected the problem that was present in the children such as the development of the logical-mathematical notions, establishing clear objectives and interesting activities.